2020
DOI: 10.2217/fvl-2019-0147
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hepatitis B Surface Antibodies in Hbv infection, Disease and Clearance

Abstract: The clinical sequelae associated with chronic HBV infection is generally regarded as a consequence of an inadequate and inappropriate immune response to active viral replication, predominantly at the T-cell level. However, recent studies on hepatitis B surface antigen (HBsAg)-specific B cells and hepatitis B surface antibody (anti-HB) responses have identified their previously unrecognized role in the pathogenesis of chronic hepatitis B (CHB). These studies have also uncovered novel therapeutic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Clinical use of LWWL has shown that it is well efficacious on anti-inflammation of chronic HBV infection (Hepatobiliary Specialized Committee of China Association of Chinese Medicine et al, 2020). In addition, a meta-analysis documented that combination of LWWL with NAs (at least for 3 months) could increase the rate of HBV DNA undetectability ( OR = 1.8–6.71, p < 0.05) and HBeAg loss ( OR = 1.83–2.04, p < 0.05) compared to single use of NAs ( He et al, 2017 ; Wang et al, 2020 ). So far, there is still lack of data on experimental anti-HBV effects and underlying mechanisms of LWWL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical use of LWWL has shown that it is well efficacious on anti-inflammation of chronic HBV infection (Hepatobiliary Specialized Committee of China Association of Chinese Medicine et al, 2020). In addition, a meta-analysis documented that combination of LWWL with NAs (at least for 3 months) could increase the rate of HBV DNA undetectability ( OR = 1.8–6.71, p < 0.05) and HBeAg loss ( OR = 1.83–2.04, p < 0.05) compared to single use of NAs ( He et al, 2017 ; Wang et al, 2020 ). So far, there is still lack of data on experimental anti-HBV effects and underlying mechanisms of LWWL.…”
Section: Discussionmentioning
confidence: 99%
“…This antiviral effect was verified in HBV-replicating mouse. HBV antigen such as HBsAg is critical for HBV to establish immune tolerance, which could facilitate the persistence of HBV infection by suppressing host immunity through the regulation of IFN-related pathway ( Jiang et al, 2014 ; Warner et al, 2020 ). LWWL had a better efficacy in suppression HBsAg production and this endow it potential to play a synergistic effect with NAs.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the OBI sample group had a higher rate of anti-HBs positivity than the HSLD comparison group (41.5% vs. 3.6%), and within the OBI group anti-HBs was more prevalent in the HBsAgNx-negative samples than among the HBsAgNx positives (45.2% vs. 28.6%). Recent reports have indicated that anti-HBs may inhibit the secretion of subviral particles [36]. Whether varying degrees of immune control might lead to a continuum of HBsAg levels below the detection limits of even highly sensitive HBsAg assays is a topic for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide analogues and immune modulators are widely-used antiviral agents that are effective in preventing the spread of infectious viruses, but these medicines have several disadvantages such as strong side effects and the development of drug resistance [ 65 , 66 , 67 ]. Currently, HBsAg has a major role in host immune escape and HBsAg together with HBV DNA levels are the hallmarks of chronic HBV infection, and HBsAg is the foundation for diagnosing infections, screening blood, and determining the cure for antiviral therapy [ 68 , 69 , 70 ]. So, HBsAg inhibitors have been extensively screened to overcome chronic HBV infection and they can be structurally divided into DHQ (dihydroquinazinone) and THP (tetrahydropyridine) classes [ 71 , 72 ].…”
Section: Mixed Tail In Viral Infectionmentioning
confidence: 99%